Analysis of Community Satisfaction Index in Acceptance of Administrative Services - Rahmad, Rahmad; Sabri, Sabri; Nasfi, Nasfi (International Journal of Social and Management Studies, 2022)
Service is the essential main task of the apparatus, as state servants and public servants, there are still many shortcomings so that when viewed in terms of quality it is still far from what the community expects, this is indicated by various public complaints through the mass media. If this condition is not responded to by the government, it will create an unfavorable image of the government itself. The main function of the government is to serve the community, so the government needs to continue to improve the quality of public services. The purpose of the study was to determine community satisfaction in receiving administrative services at the Banuhampu sub-district office, Agam district and to determine the factors that influence community satisfaction in receiving administrative services at the Banuhampu sub-district office, Agam district. The research sample is 150 respondents who are people who need administrative services at the Banuhampu District Office, Agam Regency. Analysis of research data using the Community Satisfaction Index (IKM=Indek Kepuasan Masyarakat) method. The results of this study are that all indicators which are the Community Satisfaction Index (IKM) in this study are categorized as very good, and the service unit index value is 3.4293 with the IKM value after being converted is 85.7325, so the quality of service at the Banuhampu Sub-district Office, Agam Regency category A (Very Good).